Convict police and the enforcement of British order: Policing the rum economy in early New South Wales. Issue 2 (June 2020) - Allen, Matthew
Among the many peculiarities of early New South Wales was the absence of a police force to manage a population largely composed of convicted criminals. Instead, the early Governors were forced to employ trusted convicts and ex-convicts to act as watchmen and constables and police their fellows. This article explores the history of these neglected convict police in the context of the contemporary development of modern policing in the British world. Using a case-study of a crack-down on illicit distilling under Governor King in 1805–1806, I demonstrate that the convict police were both surprisingly effective and prone to corruption, reflecting the legacy of British policing traditions and the influence of reformist ideas.